The effect of social influence and interpersonal identification on The relationship between personality and performance of agents in The multilevel marketing (mlm) industry - Shaierah Gulabdin; Toh Pei Sung; Stephen Laison Sondoh Jr.; Faerozh Madli (Zibeline International Publishing, 2022)
Purpose – The purpose of this paper is threefold: first, to examine whether there is a significant effect of interpersonal identification on the agent’s performance; second, to examine whether there is a significant mediating effect on the relationship between extraversion, agreeableness, conscientiousness, emotional stability, openness to experience, and the agent’s performance; and third, to examine whether there is significant moderating effect of social influence on the relationship between interpersonal identification and the agent’s performance. Ultimately, the researchers want to provide the agent or upline to reach a higher awareness regarding their influence on interpersonal identification between personality and the agent’s performance. Design/methodology/approach – The quantitative method was applied, and 200 questionnaires were distributed. However, only 179 were used as the final sample. This study used PLS-SEM to test the causal interactions between constructs of the proposed model. Findings – Extraversion, conscientiousness, and emotional stability were found to have constructive associations with interpersonal identification. The agent's performance is generally greatly impacted by interpersonal identification. Interpersonal identification indirectly has a considerable impact on the relationship between emotional stability and performance as well as on conscientiousness and performance. Practical implications – This study can be the MLM agent’s management aspirations in shaping the recruitment of MLM, which first focuses on the individual’s personality before involving in the MLM businesses. It will also contribute to sustaining and increasing their agent’s performance in the future and have a keen interest in the MLM industry. The relationships among agents will be improved in future. Nevertheless, they will contribute to people’s economy, specifically in Sabah. Originality/value – First, this study broadens external factors like interpersonal identification and personality traits that might influence contextual performance. Second, prior research has mostly focused on the connection between personality characteristics and sales performance. In contrast, the big five personality traits and interpersonal identification were used in this study to create relative measures of contextual performance for the agent. In Sabah, very few studies in this area have been conducted in such a setting, hence this study adds to the body of information for Sabahan academics and academicians for future study.